Microlicia indurata (Melastomataceae: Lavoisiereae), a new narrow endemic from Serra dos Pireneus, Goiás, Brazil - Almeda, Frank; Pacifico, Ricardo; Martins, Angela B.; Medeiros, João De Deus (Phytotaxa, 2023)
Microlicia indurata is described as a new species from cerrado rupestre in the Serra dos Pireneus of Goiás, Brazil. Illustrations, photos taken in the field, a distribution map, a recommended conservation assessment, and a discussion of putative related species based on morphological similarities are provided. Microlicia indurata is readily recognized by its openly branched shrubby habit, sessile elliptic-lanceolate to elliptic-ovate 5–7-nerved leaf blades that are moderately to copiously covered with short (mostly 0.5–0.7 mm) gland-tipped trichomes on both surfaces, 6-merous, solitary, sessile flowers, caducous calyx lobes that greatly exceed the hypanthia at anthesis, white petals, red antesepalous (large) anthers, 6-locular ovaries that are ca. ⅓ inferior, and mature capsules that are hard and woody with a somewhat protruding tapered acute apex. It is compared with M. pohliana, its presumed closest relative, and the superficially similar M. mucorifera and M. nervulosa.